Two Dissociable Functions of Spatial Attention, Facilitation Effect and Inhibition of Return - Yukihisa Matsuda (Current Overview on Science and Technology Research Vol. 4, 2022)
The research of visual and spatial attention from the late 20th century until today started with two important streams. The research of Michael I. Posner using the spatial cueing method is one of them. In this chapter, I introduce my research on the effect of cue duration in the facilitation effect and IOR and on the independence of those two functions of spatial attention. The first aim was to shed light on the question of how the cue duration affects the facilitation effect and IOR. The second aim was to examine the independence of the facilitation effect and IOR. To clarify this point, the relationships between the magnitude of the facilitation effect and that of IOR were examined. The results of Experiment 1 and 2 supported the notion that the facilitation effect and IOR are influenced by dissociable factors (both stimulus properties and participants’ traits) and presumably are controlled by different mechanisms.